Pengaruh Preferensi Klien dan Pengalaman Auditor terhadap Pertimbangan Auditor pada Kantor Akuntan Publik di Kota Makassar - Sufiati Sufiati; Risal Risal (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
This study aims to examine the effect of Client Preferences and Auditor Experience simultaneously and partially on Auditor Considerations at the Public Accounting Firm in Makassar City.The population in this study was 34 auditors from 7 Public Accounting Firmsin Makassar City. The sampling technique used was saturation sampling, in which the entire population was sampled, 34 auditors. Methods of data analysis used was multiple regression analysis techniques.The results of the study prove that the Client Preferences and Auditor Experience simultaneously have a positive and significant effect on Auditor Considerations in Makassar City. Client Preferences have a significant positive effect on Auditors' Considerations, whereas Auditor's Experience does not have a significant effect on Auditor Considerations at Public Accounting Firms in Makassar City.